The blue land planarian Caenoplana coerulea, an invader in Argentina - Negrete, Lisandro Hector Luis (2011)
The blue land planarian Caenoplana coerulea is reported from Argentina (Buenos Aires province). We found C. coerulea in the east central region of Argentina in anthropic environments. The specimens that we found have the characteristic of the species found in others regions; that is, a bluish dorsal surface with a yellow mid-dorsal stripe and eyes forming a single row around the anterior tip, clustered laterally. This is the first record of this species from the Neotropical Region, and together with Bipalium kewense are the only 2 species of exotic terrestrial planarians so far recorded in Argentina.